The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3892/ijmm.21.6.801
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants with atherothrombotic cerebral infarction in Japanese individuals with metabolic syndrome

Abstract: Abstract. Metabolic syndrome is a risk factor for cardiovascular disease. The aim of the present study was to identify genetic variants that confer susceptibility to atherothrombotic cerebral infarction among individuals with metabolic syndrome in order to allow prediction of genetic risk for this condition. The study population comprised 1284 unrelated Japanese individuals with metabolic syndrome, including 313 subjects with atherothrombotic cerebral infarction and 971 controls. The genotypes for 296 polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 25 publications
3
61
3
Order By: Relevance
“…This analysis showed that none of the individual studies influenced the pooled ORs, which ranged from 1.29 (95%CI = 1.08-1.55) to 1.41 (95%CI = 1.19-1.69) for T2DM and from 1.009 (95%CI = 0.897-1.135) to 1.089 (95%CI = 0.945-1.256) for obesity, indicating that the results of the meta-analysis were reliable and stable. However, the results of the meta-analysis for MetS were not stable, being more significant (P < 0.001, OR = 1.281, 95%CI = 1.182-1.389) after removing Turkovic's study, and nonsignificant after excluding studies by Vimaleswaran et al (2006), Csép et al (2007), Yamada et al (2008), or the one by Mitsutoshi et al (2007).…”
Section: Sensitivity Analysismentioning
confidence: 91%
See 3 more Smart Citations
“…This analysis showed that none of the individual studies influenced the pooled ORs, which ranged from 1.29 (95%CI = 1.08-1.55) to 1.41 (95%CI = 1.19-1.69) for T2DM and from 1.009 (95%CI = 0.897-1.135) to 1.089 (95%CI = 0.945-1.256) for obesity, indicating that the results of the meta-analysis were reliable and stable. However, the results of the meta-analysis for MetS were not stable, being more significant (P < 0.001, OR = 1.281, 95%CI = 1.182-1.389) after removing Turkovic's study, and nonsignificant after excluding studies by Vimaleswaran et al (2006), Csép et al (2007), Yamada et al (2008), or the one by Mitsutoshi et al (2007).…”
Section: Sensitivity Analysismentioning
confidence: 91%
“…The between-study heterogeneity may have arisen for one of the following reasons. First, different diagnostic criteria for MetS: IDF (Csép et al, 2007;Turkovic et al, 2012), American Heart Association/National Heart, Lung, and Blood Institute (AHA/NHLBI) (Yamada et al, 2008;Oguri et al, 2009); and Adult Treatment Panel III guidelines (ATPIII) (Vimaleswaran et al, 2006;Miller et al, 2007). Second, ethnicity differences; the T allele frequencies of controlsubject Croatians, Indians, Romanians, Han Chinese, and Japanese were 0.224, 0.269, 0.281, 0.297, and 0.329, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These particular polymorphisms also have been shown to increase the risk for restenosis following coronary stenting, as well as for hypertension and atherothrombotic cerebral infarction in Japanese (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%